Processing of Reynoutria multiflora: transformation of catechin and gallic acid derivatives and their identification - Bai, Junqi; Zou, Qiyu; Su, He; Liao, Baosheng; Wang, Ping; Huang, Juan; Zhang, Danchun; Gong, Lu; Xu, Wen; Zhang, Jing; Huang, Zhihai; Qiu, Xiaohui (Frontiers in Pharmacology, 2024)
The root of Reynoutria multiflora (Thunb.) Moldenke (RM) has been used widely in formulations of herbal medicines in China for centuries. Raw Reynoutria multiflora (RRM) should be processed before use to reduce toxicity and increase efficacy. However, detailed regulation of the processing endpoint is lacking, and the duration of processing can vary considerably. We conducted in-depth research on stilbene glycosides in RM at different processing times. Previously, we discovered that 219 stilbene glycosides changed markedly in quantity and content. Therefore, we proposed that processing causes changes in various chemical groups. To better explain the mechanism of RM processing for toxicity reduction and efficacy enhancement, we used a method of tandem mass spectrometry described previously to research gallic acid based and catechin-based metabolites. A total of 259 metabolites based on gallic acid and 112 metabolites based on catechins were identified. Among these, the peak areas of 157 gallic acid and 81 catechins gradually decreased, those of another 71 gallic acid and 30 catechins first increased and then decreased, those of 14 gallic acid and 1 catechin gradually increased. However, 17 of the gallic acids showed no significant changes. We speculate that many gallic acid metabolites hydrolyze to produce gallic acid; moreover, the dimers/trimers of catechins, after being cleaved into catechins, epicatechin, gallic acid catechins, and epicatechin monomers, are cleaved into gallic acid and protocatechualdehyde under high temperature and high humidity, subsequently participating in the Maillard reaction and browning reactions. We showed that processing led to changes in chemical groups, clarification of the groups of secondary metabolites could provide a basis for research on the pharmacological and toxic mechanisms of RM, as well as the screening of related markers.